Affricated allophones of North Welsh /t/: an acoustic analysis - Jaworski, Sylwester; Baran, Michał (Penerbit Universiti Kebangsaan Malaysia, 2023)
Welsh is a p-Celtic language spoken mostly in the British Isles. Its consonant inventory features six plosive phonemes, i.e. /p, t, k, b, d, g/. The Welsh plosives exhibit a contrast between the fortis and lenis series marked phonetically by a number of phonetic features, the most important of them being aspiration. A previous study on Welsh plosives conducted by the authors of this paper revealed that, unlike the other plosives, the Welsh /t/ has a strong tendency towards affrication in some contexts. Since affrication of plosives has received some attention in phonetic studies on other languages, it seemed striking that potential affrication of Welsh plosives has not yet been studied phonetically. The present study includes word-initial and word-final realisations of /t/ in Welsh monosyllabic lexemes. The analysis of four key spectral moments; namely, centre of gravity, dispersion, skewness and kurtosis, was conducted to confirm the assumptions regarding allophonic variation of the Welsh /t/ based on a visual inspection of spectrograms. The results suggest that the Welsh /t/ may actually have as many as four allophones, i.e. the aspirated allophone [th ], the affricated allophone [ts], which can also be aspirated in two different ways; namely, aspiration can occur simultaneously with affrication [t sh] or it can follow the affricated section [tsh ].